INFLUÊNCIA DA ACESSIBILIDADE E EXTERNALIDADE NO MERCADO IMOBILIÁRIO DOS IMÓVEIS URBANOS SITUADOS “ALÉM LINHA” NO MUNICÍPIO DE PRESIDENTE PRUDENTE - Hudson Matheus Carvalho Santos; Mayara Cristina de Paula Felipe (Colloquium Exactarum, 2015)
The municipality of Presidente Prudente had their expansion characterized by the implementation of the iron road High Sorocabana. However, this territorial expansion has taken on a highly segregated character,ie to, areas with steeper topography was earmarked populations with low purchasing power, on the other hand, the smooth plains were occupied by social classes who had a greater purchasing power. In this way, the territorial expansion was more intense west of the railroad, thus creating areas beyond the line (located east of the Railway High Sorocabana), that is held, by both the historical process of low investment by the municipality in these areas, as well as, because of the psychological barriers, caused by the iron road. In this sense, the study looked for identify the influences of factors such as: slope, accessibility and infrastructure in the value of the square meter of constructed area beyond the line.